Perception of female nursing professors about their quality of life - Amanda Miranda Cruz; Natália Gondim de Almeida; Ana Virgínia de Melo Fialho; Dafne Paiva Rodrigues; Juliana Vieira Figueiredo; Adriana Catarina de Souza Oliveira (Rev Rene)
Objective: to describe the perception of female nursing professors about their quality of life. Methods: descriptive exploratory study with a qualitative approach, performed at a public university, with 24 nursing professors, using semistructured interviews to obtain the data. Speeches were recorded, transcribed and analyzed by Minayo’s categorical analysis, with the categories: defining quality of life by female nursing professors and checking the existence of quality of life. Results: perceptions were related to balance in life, good conditions of life and stress reduction. It proved the existence of quality of life for most of them, and for those who did not have it or had it partially one mentioned problems related to the environment or to the working hours. Quality of life was related to well-being and to a sense of life satisfaction. Conclusion: quality of life of female nursing professors both in the workplace and in their personal lives stem from several factors, involving environment and interpersonal relationships.